Ivalo River Sandbanks - Langridge, L. (author) (2016)
Through an exploration of built form in a highly dynamic river environment, this project addresses the relationship between architecture, flooding, and landscape. A series of buildings are proposed along the river's banks in the small Finnish village of Ivalo, 250km above the Arctic Circle Architecture and The Built Environment Architectural Engineering and Technology Delta Interventions